Kahoot! as a learning tool in senior high school students’ reading comprehension of procedure text - Anggrarini, Natalia; Yulianawati, Ida; Ardianti, Indah (Concept : Community Concern for English Pedagogy and Teaching, 2024)
Kahoot! is used in Education as a learning tool to boost students’ motivation, evaluate learning, and increase vocabulary. Meanwhile, the urge to master the four skills of language is compulsory. Some research focused on how Kahoot! boosts students’ motivation and vocabulary, but has less to investigate specific skills such as reading. The purpose of this study is to find out the effectiveness of Kahoot! as a learning tool in reading comprehension. Grounded in Quantitative Research in the scheme of Pre-Experimental Research with one-group pre-test and post-test. This study involved 29 senior high school students of grade X. To collect the data, a Pre-test and a Post-test were designed in 20 multiple-choice questions of a reading comprehension test. The calculation was conducted using IBM SPSS Statistics 25. The results cover the pre-test results in the low category, where the average score was 66.55, which was under the minimum criteria of student completion. Kahoot! as a learning tool was then conducted, and statistical results proved that Kahoot! as a learning tool in reading comprehension is effective. It is shown that the average score of the reading comprehension was gained above the minimum criteria of student completion. It was 88.72. This result indicates that Kahoot!, as a learning tool in reading comprehension, significantly improves their reading achievement, as the students’ knowledge of the reading topic is improved by the teacher’s guidance in presenting abstract concepts found in reading. Keywords: Kahoot!; learning tool; reading comprehension; game-based learning; preexperimental design;